DETERMINAN POLITIK LUAR NEGERI, DALAM PENGAMBILAN KEBIJAKAN IMPOR BERAS INDONESIA PERIODE PEMERINTAHAN TAHUN 2009 - 2014 - Wattimena, Francine; Sushanti, Sukma; Priadarsini, Ni Wayan Rainy (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2019)
ABSTRACT   As a big country who known has many of rich nature resources, Indonesia is an agrarian country who produce many food crops for example is rice plant. Apart of surplus harvest, Indonesia government continuously do rice import from other countries for example is Thailand to fulfill the domestic stockpile. This research was made to find the things that determines the foreign policy, and also the other positive effect of the connection on the bilateral transaction between the two countries. This research was made using domestic determinant concept, foreign determinant concept, and also comparative advantage. Key Word : Indonesia – Thailand, rice, determinants of foreign policy, comparative advantage.